Gables women - Wayne, Jane E. (New York Prentice Hall Press, 1987)
These old-timers reminisced about Gables marriges, romances, flings, and affairs the broken hearts, frustrations, and indiscretions and how he tried to live up to his reputation as the greatest lover of the time.
Keywords: Biography